2006
DOI: 10.1203/01.pdr.0000238341.12229.d3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Oxidative Stress and Antioxidant Systems in the Liver of Patients With Wilson Disease: Hepatic Manifestation in Wilson Disease as a Consequence of Augmented Oxidative Stress

Abstract: ABSTRACT:The role of oxidative stress in the pathogenesis of liver disease in Wilson disease (WD), a genetic disorder characterized by excess hepatic deposition of copper that generates free radicals, remains unclear. This study investigates oxidative stress on the liver and hepatic antioxidant responses in WD using liver specimens from affected patients showing mild liver damage (group I, n ϭ 3), moderate or greater liver damage (group II, n ϭ 5), and fulminant hepatic failure (group III, n ϭ 5) and from asym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 37 publications
0
49
0
Order By: Relevance
“…Also, there is significant decrease in mitochondrial enzyme activities in livers of patients with WD as compared with patients with cholestatic liver diseases with high copper accumulation [56]. This implies that oxidative damage and mitochondrial dysfunction are important in the pathogenesis of WD [57].…”
mentioning
confidence: 99%
“…Also, there is significant decrease in mitochondrial enzyme activities in livers of patients with WD as compared with patients with cholestatic liver diseases with high copper accumulation [56]. This implies that oxidative damage and mitochondrial dysfunction are important in the pathogenesis of WD [57].…”
mentioning
confidence: 99%
“…Previous studies have shown that reduction of GPx-1 activity contributes to the development of both chronic renal failure and fulminant hepatic failure, 14,15 suggesting a protective role of the activated GPx-1-based anti-oxidant system on organ dysfunction. In our study, pre-operative b-rGSH levels were positively correlated with blood urea nitrogen levels, and negatively with cholinesterase and MAP values, supporting a link between impairment of the GSH-GPx-1 system and hepatorenal failure, an unfavorable condition for LVAD implantation.…”
Section: Discussionmentioning
confidence: 98%
“…This hypothesis is supported by studies of hepatic tissues from affected patients, which show decreased ratios of reduced to oxidized glutathione, increased lipid peroxidation products, and lower activities of antioxidant enzymes (11 ). FHF in WD is believed to be initiated by extensive apoptosis of hepatocytes triggered by extremely high loads of oxidant stress (11 ). The sudden massive release of hepatic copper precipitates hemolysis via direct damage to erythrocyte membranes, by inhibiting erythrocyte enzymes, and oxidative stress (4,5 ).…”
Section: Case Resolutionmentioning
confidence: 94%